E-COMMERCE CONSUMER BEHAVIOR AND SHOPPING CULTURE DURING THE COVID-19 PANDEMIC - Lupiana, Feri; Andika Kusumajaya, Robby (MANAJEMEN, 2021)
In the era of the Covid-19 pandemic, the marketplace platform by the nation's children dominates the online shopping market in Indonesia. Tokopedia, Shopee, Bukalapak, Lazada, and Bibli are among the top five frequented online shopping sites in Indonesia. Data from Bank Indonesia recorded electronic trade transactions almost doubled in the midst of the Covid-19 pandemic, the use of electronic money is also predicted to rise by 32.3 percent to Rp 266 trillion. In addition, digital banking transactions are expected to grow by 19.1 percent. Based on these data, it can be concluded that online shopping behavior has become a new trend, lifestyle, and culture in the Covid-19 pandemic. The data from Bank Indonesia shows the phenomenon that online shopping and conducting digital banking transactions, on the one hand, is a solution to prevent the spread of Covid-19 while on the other hand, without us knowing, consumers will become "dark eyes" so that it becomes consumptive, excessive shopping, and buying goods / services beyond the limits of needs.